2018
DOI: 10.1111/jmi.12680
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards a methodology for high throughput 3D reconstruction of soot nanoparticles via electron tomography

Abstract: The aim of this work is to make progress towards the development of 3D reconstruction as a legitimate alternative to traditional 2D characterization of soot. Time constraints are the greatest opposition to its implementation, as currently reconstruction of a single soot particle takes around 5-6 h to complete. As such, the accuracy and detail gains are currently insufficient to challenge 2D characterization of a representative sample (e.g. 200 particles). This work is a consideration of the optimization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Okyay's SEM tomography study of soot used a simple sphere model, and observed no elongation for a ±80° reconstruction [64]. Our own study performed similar work and saw 15% Z-elongation for ±60° reconstruction of a sphere [63]. It is common for simplified structures to be used as model systems due to difficulties associated with the creation of synthetic data-sets.…”
Section: Electron Tomography For Soot Nanoparticlessupporting
confidence: 53%
See 4 more Smart Citations
“…Okyay's SEM tomography study of soot used a simple sphere model, and observed no elongation for a ±80° reconstruction [64]. Our own study performed similar work and saw 15% Z-elongation for ±60° reconstruction of a sphere [63]. It is common for simplified structures to be used as model systems due to difficulties associated with the creation of synthetic data-sets.…”
Section: Electron Tomography For Soot Nanoparticlessupporting
confidence: 53%
“…At this point, three variations of each tilt-series were made for each model: the full ±80° tilt-series (161 images), a ±60° tilt-series (121 images), and a ±60° tilt-series with 3° increments (41 images; henceforth referred to as ±60_3°). These represent the maximum tilt series that can be reconstructed with the IMOD/Etomo software (±80°), the largest tilt range that can routinely be recorded experimentally with TEM (±60°), and the optimum tilt-series as per our previous publication (±60° with 3° increments) [63]. Figure 3 shows an example of images from a simulated tilt-series For each of the models, all 3 tilt-series were reconstructed and tomograms produced (39 reconstructions total).…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations